Rekonstruksi Metodologi Penelitian Filsafat - Yohanes Orong (IAIN SYEKH NUR JATI, 2023)
This article aims to describe the re-construction of procedures and schemes of philosophy research methodology. The study is motivated by the problem of research methodology in philosophy colleges and faculties. The methodological problem is caused by the assumption that in matters of research or writing scientific papers, the rules of research in philosophy are different from research in other fields of science. Because philosophy is different from other sciences, a philosophy researcher ignores the methodological demands that researchers of other sciences adhere to. Against this assumption, the most appropriate question is what exactly is the scheme of philosophical research and the provisions that make philosophical research methods different from other fields of science? The article seeks to prove the above assumption. Using descriptive qualitative research methods, in addition to bringing to the fore the veil of philosophical research methodology issues in philosophy schools, the article in the final section re-explains with some important emphasis the essence of philosophical research methodology. In this section, four main elements are outlined, namely the nature of philosophical research methodology, the cross-disputes of scientific methods and philosophical methods, the reaffirmation of the nature of philosophical research as pluralistic and qualitative, the methodological dialog of philosophy and other sciences, and philosophical research schemes.